(3QSGdI aj GdJLhjOs - (3eMeO Hf ejQRG Hf eMeO GdSeQbfOjs
(3ChdgG (B:s
(3GdMeO ddg GdPj cTa GdZWGA HJfRjd cJGHg CeG HYO agPg GdQSGdI eTJedI Ydi GdHGHjf; GdHGH GdChd aj HjGf JLhjO GdbQBf GdHGH GdKGfj aj HjGf eSGFd GdeJaQbIs
(3BNQgG (B:s
(3GdNGJeI(B: (3GYde Cf hUd eY BNQ GdShQI Ef cGf BNQ GdShQI SGcf hgeRI Gddg CcHQ YfO GdhUd eMPha, hGddg CYdes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs